Monism in Indian philosophy: the coherence, complexity, and connectivity of reality in Śaṃkara's arguments for Brahman. (October 2022) - Frazier, Jessica
Abstract: Classical Indian thought contains a number of arguments for monism that reject the cogency of metaphysical pluralism's account of change, development, and causation in the world. They do this on the basis of (a) the coherence of changes that we see in the world, (b) the difficulty of limning absolute distinctions between individuals, and (c) the prerequisite need for some medium explaining causal interactions. This article provides some background to Indian philosophical thought about a basic fabric of reality that grounds changing forms, containing the telos of their evolution in potentia . It then sets out Coherence, Complexity, and Connection Arguments for monism as employed by the Vedāntic scholastic philosopher Śaṃkara. Along the way, we clarify the Vedāntic conception of a single material, efficient, and formal cause that provides a medium for connection and combination, is naturally replete with generative order and impetus, and in which the teloi of all forms are embedded. We will briefly consider what the argument shows, if it succeeds – comparing with current philosophical approaches to monism. Finally, we observe that this rich monism, describing a single vertiginous reality of many levels and powers, is central to classical Hindu conceptions of what makes something 'divine'.